Tajikistan Jobs Diagnostic : Strategic Framework for Jobs - Strokova, Victoria; Ajwad, Mohamed Ihsan (World Bank, Washington, DC, 2017)
Tajikistan’s economy is not creating sufficient jobs for its rapidly growing workforce, in particular its burgeoning youth population. As a result, its most valuable asset – human capital – is largely underutilized. Although remittance-driven growth since the early 2000s has led to a steep decline in the poverty rate, poverty remains high. Strong economic growth in the last decade has not resulted from structural transformation that can lead to sustained improvements in the standard of living. Jobs have been created, but these are mainly in low-productivity activities, often in the informal sector. In addition, there are major inequalities in terms of labor market outcomes between population groups and across regions. The report, “Tajikistan Jobs Diagnostic: Strategic Framework for Jobs”, analyzes the main challenges the country faces in creating jobs at the macro, firm, and household levels. It also sets out policy recommendations to enable the country to create more and better jobs that are also more inclusive of women, youth, and other vulnerable population groups.